2006
DOI: 10.1002/pola.21619
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembled lipid nanotube hosts: The dimension control for encapsulation of nanometer‐scale guest substances

Abstract: Supramolecular nanotube hosts with precisely controlled inner or outer diameters have been synthesized by self-assembly of unsymmetrical bolaamphiphilic monomers or glucopyranosylamide lipids, respectively. Time-resolved fluorescent measurement using 8-anilinonaphthalene-1-sulfonate (ANS) as a probe revealed that the water confined in a cardanyl-b-D-glucopyranoside lipid nanotube has relatively lower solvent polarity corresponding to that of propanol than bulk water. Extensively developed hydrogen bond network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 107 publications
0
58
0
Order By: Relevance
“…Organic nanotubes can entrap proteins, nucleic acids, viruses, and metal nanoparticles, which cannot be achieved using cyclodextrin because organic nanotubes have at least a 10-fold larger inner diameter providing much greater space for the encapsulation of passenger molecules than cyclodextrin. Similar to cyclodextrin, organic nanotubes are expected to be applied for use in the medical and food fields (Yang et al, 2004a,b;Yui et al, 2005;Shimizu, 2006Shimizu, , 2008aKameta et al, 2005Kameta et al, , 2007Kameta et al, , 2008.…”
Section: Introductionmentioning
confidence: 98%
“…Organic nanotubes can entrap proteins, nucleic acids, viruses, and metal nanoparticles, which cannot be achieved using cyclodextrin because organic nanotubes have at least a 10-fold larger inner diameter providing much greater space for the encapsulation of passenger molecules than cyclodextrin. Similar to cyclodextrin, organic nanotubes are expected to be applied for use in the medical and food fields (Yang et al, 2004a,b;Yui et al, 2005;Shimizu, 2006Shimizu, , 2008aKameta et al, 2005Kameta et al, , 2007Kameta et al, , 2008.…”
Section: Introductionmentioning
confidence: 98%
“…60 Furthermore, confined water in the LNT hollow cylinder of 4 with 10 nm inner diameters proved to exhibit the physical properties of structured water similar to intracellular water. 61,62 In our early work, we found that capillary action enables the LNTs to encapsulate aqueous solutions or dispersions containing such guest substances into their internal hollow cylinders.…”
Section: Hollow Cylinders That Can Encapsulate Biomacromolecular Guestsmentioning
confidence: 99%
“…One has never needed to address those diverse factors to tailor advanced supramolecular nanotube hosts when designing conventional low-molecular-weight host compounds. 60 To achieve passive encapsulation of the guests independent of capillary action, we have started with rational modification of the LNT inner surface with designed functionalities as well as charges.…”
Section: Hollow Cylinders That Can Encapsulate Biomacromolecular Guestsmentioning
confidence: 99%
“…Apart from the surface modification of lipid tubes, encapsulation and embedding of appropriate nanoparticles into hollow cylinder and membrane lamella of lipid tubes, respectively, were studied by Shimizu's group 29,30 . They have succeeded in filling gold and silver nanoparticles into lyophilized lipid nanotubes to realize the 1-D arrangement of the nanodots that are shown in Figure 3b.…”
Section: Encapsulation or Embedding Of Nanoparticles In Lipid Tubesmentioning
confidence: 99%